Assessing the impact of an avian flu impact in Kenya - Thurlow, James (International Food Policy Research Institute, 2009)
While some African countries have not yet experienced outbreaks of highly pathogenic avian influenza (HPAI), they remain vulnerable, both in terms of susceptibility and potential economic losses. Kenya is one of these vulnerable countries. Its position along migratory bird routes and proximity to other high risk countries make Kenya particularly susceptible to a potential HPAI outbreak. The threat of avian flu has caused many households in Kenya to limit their consumption of poultry products and the Kenyan government has also banned poultry imports (Nyaga, 2007; Omiti and Okuthe, 2009). Thus, even without a confirmed outbreak, avian flu may undermine the poultry sector with adverse impacts on agricultural livelihoods.